A Report on Fowl Cholera and Taeniasis Infection in a Backyard Flock - Sushma, H.R; N. Pazhanivel; N. Jayanthi; Ganne Venkata Sudhakar Rao (The Indian Veterinary Journal, 2025)
A two-year-old Aseel cock from a backyard flock was presented for post-mortem examination, at the Department of Veterinary Pathology, Madras VeterinaryCollege, Chennai. Gross lesions were enlarged, and congested liver with multiple multifocal variable sized necrotic foci in the liver, congestion of spleen and pinpoint hemorrhages in the proventriculus.The intestine had mucus mixed contents with tapeworms identified as Raillietinaechinobothrida. The samples collected were subjected for cytological,bacteriological and histopathological examination and these findings were suggestive of pasteurellosisand was further confirmed by culturalcharacterization and PCR assay.